2005
DOI: 10.1002/bit.20433
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and proteolysis of the Zb‐MalE and Zb‐MalE31 proteins during overproduction in Escherichia coli

Abstract: From the hypothesis that the rate of expression of a nascent polypeptide controls the accumulation of soluble full-length protein, accumulation of the model fusion proteins Zb-MalE and Zb-MalE31, were studied. MalE and MalE31 are two isoforms of the maltose binding protein, differing only in two consecutive amino acids. Parameters controlling the expression rate were the transcription rate, which was controlled by IPTG induction of the lacUV5 promoter and the substrate addition levels during fed-batch cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…At a growth rate of 0.2 h -1 , about 45% of the product was correctly formed and this amount was decreased to 30% when the growth rate increased to 0.5 h -1 . We have also been able to show that the degree of proteolysis and inclusion body formation becomes higher with higher growth rate [1], which implicated that the higher the growth rate the lower the percentage of the soluble protein product. Present data makes it thus seem likely that a high productivity is inversely proportional to the final protein quality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At a growth rate of 0.2 h -1 , about 45% of the product was correctly formed and this amount was decreased to 30% when the growth rate increased to 0.5 h -1 . We have also been able to show that the degree of proteolysis and inclusion body formation becomes higher with higher growth rate [1], which implicated that the higher the growth rate the lower the percentage of the soluble protein product. Present data makes it thus seem likely that a high productivity is inversely proportional to the final protein quality.…”
Section: Discussionmentioning
confidence: 94%
“…This strategy would also give another benefit. Several authors have shown that the glucose feed rate is a major parameter influencing not only the specific productivity but also the solubility and proteolysis rate of a protein product [1,2]. In this way we could therefore further increase the number of production technologies and widen the techniques to be used in the high throughput format.…”
Section: Introductionmentioning
confidence: 98%
“…Because many human proteins, including human IFN-a, are frequently expressed as the inclusion body (Babu et al 2000;Khalilzadeh et al 2004;Lim et al 2004;Panda 2003;Panda et al 1999;Schmidt et al 1999), it is necessary to modulate the tendency towards insolubility in order to improve functional protein expression levels. Soluble expression levels of recombinant proteins can Manderson et al 2006;Sandén et al 2005;Striedner et al 2003) by adjusting the amount of inducer added to the medium and/ or varying the growth rate in order to modulate transcription. One example includes the expression of recombinant IFN-a at suboptimal temperatures, in which an improvement in soluble protein expression was assigned to an inhibition of the overall protein synthesis rate (Hoffmann et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this have been explained by the findings that the expression levels were higher than the threshold of their solubilities in the cytoplasm and/or the environment in the cytoplasm did not allow the correct folding of recombinant protein [26][27][28]. There have recently been several reports that the modulation of the transcription rate through adjustment of the amount of inducer and/or modification of the growth rate led to the improvement of the expression level of soluble recombinant protein [29][30][31]. Furthermore, it was shown that a higher protein synthesis rate affected the quality of the expressed protein with respect to solubility, enzymatic activity, and proteolysis [31][32][33][34].…”
Section: Introductionmentioning
confidence: 94%
“…There have recently been several reports that the modulation of the transcription rate through adjustment of the amount of inducer and/or modification of the growth rate led to the improvement of the expression level of soluble recombinant protein [29][30][31]. Furthermore, it was shown that a higher protein synthesis rate affected the quality of the expressed protein with respect to solubility, enzymatic activity, and proteolysis [31][32][33][34]. Previously, we modulated the tendency towards inclusion body formation of recombinant interferon-α via the addition of glucose [35].…”
Section: Introductionmentioning
confidence: 99%